Profesi Host yang Tercermin dalam Manga Hosutan e Youkoso Karya Makoto Tateno - Rica Garwita Juniari, Ni Putu; Ari Sulatri, Ni Luh Putu (Humanis; Vol 22 No 2 (2018), 2018)
This research ’s title is “ Host Profession which had Reflected in Manga Hosutan e Youkoso by Makoto Tateno” . This research a imed to know the criteria to be a host in a host club in Japan. This research used the sociology of literature theory by Ratna (2009) , literary trilogy theory by Wellek and Warren (199 3 ), and semiotics theory by Danesi (201 2 ). The results of this research showed that there are two criteria to be a host , i.e. physical criteria and non-physical criteria . In detailed, has an attractive face and has a good looking respectively. On the other hand, there are five parts of non-physical criteria to be a host, which have tolerance to alcoholic beverages, have skills to communicate with costumers, have a broad insight, adjusted well with costumer needs, and should be between 20 years to 30 years. Host profession which had reflected in manga Hosutan e Youkoso are host assignment, host level, working hours of host, host earnings, host identity, and host club. There are three parts of host assignment, i.e. welcoming costumers, assisting the costumers, and giving attention to costumers. Moreover, there are two parts of host level, that are number one host and host as herupu ‘a junior host who help the number one host in host club’.